Senegalia montis-salinarum, a new species of Fabaceae: Mimosoideae endemic to the Soutpansberg, South Africa - Hahn, Norbert (Phytotaxa, 2016)
Senegalia montis-salinarum is a proposed new species, related to S. burkei. This species was found to be a distinct edaphic entity, endemic to the Soutpansberg Centre of Endemism. This article also clarifies some taxonomic problems within the Senegalia burkei complex.